Moxonidine-based combination antihypertensive therapy in patients with metabolic syndrome - E. V. Tishina; V. B. Mychka; M. A. Saidova (Кардиоваскулярная терапия и профилактика, 2012)
Aim. To assess the effects of moxonidine-based combination therapy on clinical status, laboratory parameters, and target organs in patients with metabolic syndrome (MS). Material and methods. In total, 60 MS patients with Stage 1-2 arterial hypertension (AH) were randomised into 3 groups. Group I was administered moxonidine (0,2-0,4 mg/d) and amlodipine (5-10 mg/d); Group II received moxonidine (0,2-0,4 mg/d) and hydrochlorothiazide (12,5 mg/d); Group III was treated with moxonidine (0,2-0,4 mg/d) and enalapril (10-20 mg/d). At baseline and after 24 weeks of treatment, the following characteristics were assessed: waist circumference (WC), body mass index (BMI), 24-hour blood pressure monitoring (BMP) parameters, left ventricular myocardial mass index (LVMMI), E/A ratio, isovolumetric relaxation time (IVRT), deceleration time (DT) of early diastolic velocity, peak Em velocity at interventricular septum and lateral wall levels, E/Em ratio (myocardial tissue Doppler echocardiography), pulse wave velocity (PWV) between descending aorta and aortic bifurcation levels (ultrasound method), and stiffness index β of ascending aorta. In addition, lipid, carbohydrate, and purine metabolism parameters were assessed; glomerular filtration rate (GFR) was calculated (MDRD method); and urine albumin levels were measured. Results. In Group I (moxonidine + amlodipine), target blood pressure (BP) levels were achieved in 70% of the patients. Systolic BP (SBP) levels, LVMMI, and DT decreased by 19,3±11,4 mm Hg, 4,4 g/m2 (p=0,09), and 10,6 ms (p<0,05), respectively. The increase in E/A ratio and Em annular velocity (Em av) reached 0,4 (p<0,05) and 1,4 cm/s (p<0,05), respectively, while E/Em av ratio decreased by 0,8 (p<0,05), and PWV decreased by 1,6 ms (p<0,05). The BMI decrease reached 0,7 kg/m2 (p<0,05). In Group II (moxonidine + hydrochlorothiazide), target BP levels were achieved in 40% of the participants, with a decrease in SBP levels by 14,7 mm Hg (p<0,05). DT was reduced by 9,4 ms (p<0,05), E/A ratio increased by 0,1 (p<0,05), while PWV, BMI, and GFR decreased by 1,3 m/s (p<0,05), 0,8 kg/m2 (p<0,05), and 5,6 ml/min/1,73 m2 (p<0,05), respectively. In Group III (moxonidine + enalapril), 60% of the patients achieved target BP levels, and SBP levels were reduced by 21,1 mm Hg (p<0,05). LVMMI decreased by 5,1 g/m2 (p<0,05), Em av increased by 0,3 cm/s (p<0,05), while the respective reduction in PWV, WC, and BMI reached 1,1 m/s (p<0,05), 1,8 cm (p<0,05), and 0,5 kg/m2 (p<0,05). All three groups demonstrated a significant reduction in urine albumin levels. Conclusion. The moxonidine-based combination therapy effectively reduced the levels of BP and urine albumin. The combination of moxonidine with amlodipine or enalapril improved cardiac structure and function, as well as renal excretory function. The combination of moxonidine and hydrochlorothiazide, however, negatively affected renal excretion. All three variants of combination therapy were metabolically neutral and demonstrated beneficial effects on visceral obesity.